Improving Nursing Students’ Speaking Skill through TikTok Application - Susiana Kaban; Vitri Rokhima (PT Inovasi Pratama Internasional, 2023)
Tik Tok application is attached and close to school-age students. It is suspected that the Tik Tok application is an interactive matter for students. Based on these indications, it can be concluded that the Tik Tok application meets the criteria of a good learning media, which is interesting and close to students, especially in English language learning. Therefore, it is necessary to have new variations in the application of interactive and effective learning media in order to influence student learning motivation in improving speaking skill. This community service event aimed to improve nursing students speaking skill through TikTok Application. This community service event was carried out by collecting descriptive and qualitative data which are then analyzed and processed to produce solutions to problems faced by the partners. The result of this event showed that 76% of the participants were motivated to perform English speaking skill through TikTok application.